Pesan Moral Puasa ‘Asyura dalam Pengamalan Ibadah Masyarakat Desa Paringgonan Kecamatan Ulu Barumun Kabupaten Padang Lawas - Burhanuddin Siregar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
This research aims to find out the moral message of fasting 'Asyura in Paringgonan’s society, Ulu Barumun, Padang Lawas. There are 3 moral messages that grow from fasting 'Asyura: 1) The moral message of religion in fasting 'Asyura is to get closer to Allah SWT and His Messenger, follow the sunnah of the Prophet, erase sins a year ago, get used to fasting sunnah especially on fasting 9, 10, 11 Muharram in the Hijri year, then you can remember the story and journey of Noah as. 2) The social moral message of fasting 'Asyura Pada is to be able to establish friendship, help each other (making 'Asyura porridge), work hand in hand, share with each other, when making 'Asyura porridge can tell each other about each other's life stories, then can joking jokingly while stirring the porridge 'Asyura so that it does not feel the fasting 'Asyura. 3) The moral message of the fasting culture of 'Asyura is by getting used to and teaching children and grandchildren and the community to fast 'Asyura on the 10th of Muharram every year, then sharing food in making 'Asyura porridge' is good to orphans, the poor, and other communities